Dewatering of algal suspension using microfiltration with cross flow in the presence of magnetite as a filter aid. (16th February 2020) - Kitani, Hidemi; Demura, Mikihide; Morisada, Shintaro; Ohto, Keisuke; Kawakita, Hidetaka
Abstract: Dewatering algal suspensions is an important step in the extraction of oil and other useful substances from algae. In this study, spherical Nannochloropsis sp. and ellipsoidal Monoraphidium sp. suspensions were dewatered in the presence of different amounts of 350‐nm magnetite particles using a microfiltration membrane with 360‐nm pores in cross‐flow mode. Magnetite functions as a filter aid by reducing the deformation of the cake of filtered algae on the membrane and providing paths for water to flow through the filtration cake of algae. In the case of Nannochloropsis sp., the highest dewatering rate was obtained when the number ratio, defined based on the size and ideal density, between Nannochloropsis sp. and magnetite was 1:12.5, but the addition of magnetite had no observable effect on the filtration of ellipsoidal Monoraphidium sp. suspensions through the membrane. After dewatering, magnetite was effectively separated from the concentrated algal suspension by the application of a magnetic field in an open flow system. Magnetite has the potential to enhance dewatering performance using a cross‐flow membrane system.